Horizontal ridge augmentation using xenogenous bone graft—systematic review - de Azambuja Carvalho, Pedro Henrique [UNESP]; dos Santos Trento, Guilherme [UNESP]; Moura, Lucas Borin [UNESP]; Cunha, Giovanni [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira-Filho, Valfrido Antônio [UNESP] (Springer Nature, 2019)
Purpose: This study aimed to perform a systematic review about the use of xenogenous bonegraft in horizontal ridge augmentation to answer the following question: In implant patients, treated with xenografts for horizontal ridge augmentation, what would be the outcomes in terms of bone gain, bone resorption, implant survival, and complication rates? Methods: The main search was performed at PubMed, Cochrane, and Scopus databases, and found 2610 articles. After selection and duplicate removal, 29 studies were included in the final review. The collected data were sample size, number and type of graft, site, horizontal gain, resorption rate, and complications. Results: A total of 610 patients were submitted to 853 bone grafts, both in the maxilla and mandible. Most studies (n = 26) used particulate grafts, isolated or associated with autogenous bone, and covered by collagen membrane or titanium mesh. The mean of horizontal bone gain was 4.44 mm. In addition, the augmented ridges allowed placement of 1325 successful dental implants. The complication rate was 7.85%, and membrane exposure was the most reported complication. Conclusions: Although the autogenous bone graft remains as the gold standard for alveolar reconstruction, this review suggests that xenogenous bone graft is a feasible alternative for horizontal bone augmentation.
Keywords: Alveolar bone loss; Alveolar ridge augmentation; Bone substitutes; Systematic review